STUDI KELAYAKAN IMPLEMENTASI SISTEM INFORMASI KLINIK MATA MOJOAGUNG MENGGUNAKAN INFORMATION ECONOMICS - Kristanto, Bagus Kristomoyo (DINAMIKA DOTCOM, 2018)
An Investment Information Systems Information Technology (IT / SI) generally require a feasibility study as well as the calculation of benefits and advantages before the investment. Several approaches are used to calculate the benefits and advantages of IT investment / SI, one of which is the Information Economics (IE) Approaches Information Economics is used in the analysis of an IT investment / SI and the development of Traditional Cost and Benefit Analysis (TCBA) involving factors economically justified business and technology in the form of financial, benefits, and risks of IT / SI them. Excellence IE method lies in its ability to take into account the benefits that half of tangible and intangible that is often overlooked by the management. The results of the feasibility study on patient and service system information at Mojoagung Eye Clinic the investment worth to implementation because give benefit such as ROI of 22.50%, and the payback period between 4 and 5 years after investment. Keywords: Information Systems, feasibility study, Information Economics